Meeting a Brilliant but Quirky Mind: Insights Offered by Infant Research. Issue 1 (1st January 2020) - Harrison, Alexandra Murray
ABSTRACT: This paper focuses on the "moving along process" toward "moments of meeting" identified in the Boston Process of Change Study Group's "Something More" paper. Insights from infant research–Tronick's dynamic description of "match, mismatch, and repair" and Beebe's model of vocal rhythm coordination–will be used to explore the "moving along process" that can lead to a "moment of meeting". These theoretical considerations will be illustrated with clinical material from the psychoanalytic treatment of a 3-4 year-old boy. The author suggests that these insights into psychoanalytic process derived from infant observation research are useful to understanding therapeutic change and may in some ways be more helpful than focusing on a specific psychoanalytic theory or technique.